2008
DOI: 10.1109/tnn.2008.2003187
|View full text |Cite
|
Sign up to set email alerts
|

Color Image Discriminant Models and Algorithms for Face Recognition

Abstract: This paper presents a basic color image discriminant (CID) model and its general version for color image recognition. The CID models seek to unify the color image representation and recognition tasks into one framework. The proposed models, therefore, involve two sets of variables: a set of color component combination coefficients for color image representation and one or multiple projection basis vectors for color image discrimination. An iterative basic CID algorithm and its general version are designed to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(47 citation statements)
references
References 36 publications
0
47
0
Order By: Relevance
“…For the CID method, we implemented its extended version based on the RGB color space [2]. In addition, following the same parameter values as used in [2], the initial value of the CID algorithm and convergence threshold were set to '[1/3,1/3,1/3]' and '0.1', respectively.…”
Section: Evaluation Of Our Methods Under Different Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…For the CID method, we implemented its extended version based on the RGB color space [2]. In addition, following the same parameter values as used in [2], the initial value of the CID algorithm and convergence threshold were set to '[1/3,1/3,1/3]' and '0.1', respectively.…”
Section: Evaluation Of Our Methods Under Different Challengesmentioning
confidence: 99%
“…Recently, considerable research work in face recognition (FR) has shown that facial color information can be used to considerably improve FR performance, compared to the FR methods relying only on grayscale information [1][2][3][4][5][6][7]. In particular, it has been reported in [5][6] that the effectiveness of color information can become significant for improving FR performance when face images are taken under strong variations in illumination, as well as with low spatial resolutions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Facial analysis can be used with context based to come out with different new features in HCI which will have lots of commercial applications. Example for this context based gesture analysis [28] is [15].The objective of the proposed work is to detect and recognize various hand gestures and special hand gestures that are present in a given image and use for automation. This Hand Gesture Recognition technique is fast (easy to calculate the orientation histograms), robust to illumination changes and takes less processing time due to little training.…”
Section: Context Based Workingmentioning
confidence: 99%
“…Facial analysis is a sub domain of the main problem in the computer vision i.e. making computer to imitate human eye [28]. This facial analysis can be a good step solves that problem.…”
Section: Improving Computer Visionmentioning
confidence: 99%